1990
DOI: 10.1007/bf01316320
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense in the eggs and embryos of antarctic sea stars (Echinodermata)

Abstract: Abstract. Fifteen species of reproductively mature echinoderms (11 sea stars, 3 sea urchins, 1 sea cucumber) were collected from McMurdo Sound, Antarctica, during austral spring and summer of 1985 and 1986; eggs and embryos were obtained, and were tested for ichthyonoxicity using the common marine killifish Fundulus grandis as a model predator. Chemical deterrents occurred in the large, yolky eggs of the pelagic lecithotrophic sea star Perknasterfuscus and the planktotrophic sea star Porania antarctica. Broode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Additionally, laboratory investigations have shown that many invertebrate larvae possess behavioral (Forward 1977, Morgan 1987, morphological (Pennington & Chia 1984, Morgan 1989, Morgan & Christy 1996, and/or chemi-cal (Lucas et al 1979. Young & Bingham 1987, McClintock & Vernon 1990, Lindquist et al 1992, Lindquist 1996, Lindquist & Hay 1996 traits that reduce their susceptibility to predators. Therefore, larvae of different invertebrates may differ dramatically in their vulnerabilities to predators.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, laboratory investigations have shown that many invertebrate larvae possess behavioral (Forward 1977, Morgan 1987, morphological (Pennington & Chia 1984, Morgan 1989, Morgan & Christy 1996, and/or chemi-cal (Lucas et al 1979. Young & Bingham 1987, McClintock & Vernon 1990, Lindquist et al 1992, Lindquist 1996, Lindquist & Hay 1996 traits that reduce their susceptibility to predators. Therefore, larvae of different invertebrates may differ dramatically in their vulnerabilities to predators.…”
Section: Introductionmentioning
confidence: 99%
“…In allopatric approaches, the predator has had no prior exposure to defensive chemicals of the prey over evolutionary time and would not have acquired resistance or learned aversion. 33 On the other hand, the sympatric approach evaluates whether chemical deterrents are effective against ecologically relevant predators. 34 The dual approach is best if possible, 35 and could test the magnitude of the defensive action of a particular extract or metabolite from a particular species.…”
Section: Resultsmentioning
confidence: 99%
“…The allocation of defensive chemistry within reproductive tissues has previously been observed in some asteroids and molluscs (Lucas et al, 1979;Pawlik et al, 1988;McClintock and Vernon, 1990;Avila and Paul, 1997). These defenses may reduce predation on the gametes after they have been deposited or released into the water column.…”
Section: Discussionmentioning
confidence: 99%